IMPLEMENTASI PROTOKOL PENCEGAHAN PENYEBARAN COVID-19 PADA PROYEK KONSTRUKSI JALAN - Angelina Eva Lianasari; Soandrijanie Linggo (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2023)
The ongoing COVID-19 pandemic is yet to be resolved, and according to epidemiologists, a third wave of the outbreak was expected to occur in February–March 2022. During August–September 2022, the rate of daily COVID-19 exposure in Indonesia remained high. The Indonesian Doctors Association (PB IDI) reported a 36-fold increase in COVID-19 cases in Indonesia, from 107 cases in early May 2022 to 3,949 cases daily. Yogyakarta is the sixth most affected province in Indonesia in terms of COVID-19 exposure. Therefore, it is crucial to examine the implementation of COVID-19 Occupational Health and Safety (OHS) practices in construction projects, specifically in the case of road construction. The Planjan-Baron-Tepus Road and Jogja-Bawen Toll Road are the projects selected for data collection, using observational methods and purposive sampling. Occupational Health and Safety is part of the company's management system, which aims to manage work activity risks and create a safe, efficient, and productive workplace. The survey results indicate that the instrument used is reliable and valid. The management has effectively implemented and communicated COVID-19 prevention measures, and the construction workers are satisfied. The workers show high motivation, awareness, and knowledge in reducing the spread of COVID-19. The workers in Planjan-Baron-Tepus Road construction strictly adhere to personal health protocols in their daily behavior. However, workers in Jogja-Bawen toll road construction are less obedient and require further motivation to be classified as highly obedient.